Cordierite formation during the experimental reaction of plagioclase with Mg-rich aqueous solutions - Hövelmann, J.; Austrheim, H.; Putnis, Andrew (Springer, 2014)
The reaction between plagioclase (labradorite and oligoclase) and Mg-rich aqueous solutions was studied experimentally at hydrothermal conditions (600–700 °C, 2 kbar). During the experiments, plagioclase grains were readily converted to cordierite and quartz within 4 days. The cordierite crystals had well-developed polyhedral shapes, but showed skeletal internal morphologies suggestingthat the initial growth occurred fast under high-driving-force conditions. In pure MgCl2 solutions (0.5–5 M), plagioclase dissolution and cordierite precipitation were spatially uncoupled indicating that Al was to some extent mobile in the fluid. Cordierite crystals formed at 700 °C showed orthorhombic symmetry, whereas those formed at 600 °C dominantly persisted in the metastable hexagonal form suggesting a strong increase in Al, Si ordering speed between 600 and 700 °C. The thermodynamic evolution of the fluid–solid system ultimately resulted in stabilization of Ca-rich plagioclase as demonstrated by partial anorthitization of unreacted plagioclase grains. Cordierite was also observed to form when Mg was added to a potentially albitizing Na-silicate-bearing solution. In that case, cordieriteprecipitation appeared to be more closely coupled to plagioclase dissolution, and secondary alteration of remnant plagioclase grains did not occur most likely due to armouring of the plagioclase by the cordierite overgrowth. The fast reaction rates observed in our experimental study have potential implications for Mg-metasomatism as a rockforming process.